ALMA finds dew drops in the dusty spider’s web - Gullberg, Bitten; Lehnert, Matthew D.; De Breuck, Carlos; Branchu, Steve; Dannerbauer, Helmut; Drouart, Guillaume; Emonts, Bjorn; Guillard, Pierre; Hatch, Nina A.; Nesvadba, Nicole P.H.; Omont, Alain; Seymour, Nick; et al. (EDP Sciences, 2016)
We present 0.̋5 resolution ALMA detections of the observed 246 GHz continuum, [CI] 3P2→3P1 fine structure line ([CI]2–1), CO(7–6), and H2O lines in the z = 2.161 radio galaxy MRC1138-262, the so-called Spiderweb galaxy. We detect strong [CI]2–1 emission both at the position of the radio core, and in a second component ~4 kpc away from it. The 1100 km s-1 broad [CI]2–1 line in this latter component, combined with its H2 mass of 1.6 × 1010 M⊙, implies that this emission must come from a compact region <60 pc, possibly containing a second active galactic nucleus (AGN). The combined H2 mass derived for both objects, using the [CI]2–1 emission, is 3.3 × 1010 M⊙. The total CO(7–6)/[CI]2–1 line flux ratio of 0.2 suggests a low excitation molecular gas reservoir and/or enhanced atomic carbon in cosmic ray dominated regions. We detect spatially-resolved H2O 211−202 emission – for the first time in a high-z unlensed galaxy – near the outer radio lobe to the east, and near the bend of the radio jet to the west of the radio galaxy. No underlying 246 GHz continuum emission is seen at either position. We suggest that the H2O emission is excited in the cooling region behind slow (10–40 km s-1) shocks in dense molecular gas (103−5 cm-3). The extended water emission is likely evidence of the radio jet’s impact on cooling and forming molecules in the post-shocked gas in the halo and inter-cluster gas, similar to what is seen in low-z clusters and other high-z radio galaxies. These observations imply that the passage of the radio jet in the interstellar and inter-cluster medium not only heats gas to high temperatures, as is commonly assumed or found in simulations, but also induces cooling and dissipation, which can lead to substantial amounts of cold dense molecular gas. The formation of molecules and strong dissipation in the halo gas of MRC1138-262 may explain both the extended diffuse molecular gas and the young stars observed around MRC1138-262.